15.2k views
2 votes
Someone help please thank you

Someone help please thank you-example-1

1 Answer

2 votes

Answer:

See below.

Explanation:

So we have the two functions:


f(x)=8x-5\text{ and } g(x)=9-2x

And we want to find:


(f\circ g)(x)\text{ and } (g\circ f)(x)

1)

Recall that:


(f\circ g)(x)

is the same as:


=f(g(x))

Thus, we can substitute g(x):


=f(9-2x)

And substitute that into f(x):


f(x)=8x-5\\f(9-2x)=8(9-2x)-5

Distribute:


=72-16x-5

Subtract and simplify:


=67-16x\\=-16x+67

Thus:


(f\circ g)(x)=-16x+67

2)

Similarly:


(g\circ f)(x)=g(f(x))

Substitute f(x):


g(f(x))=g(8x-5)

Substitute:


g(8x-5)=9-2(8x-5)

Distribute:


=9-16x+10

Simplify:


=-16x+19

Therefore:


(g\circ f)(x)=-16x+19